MENINGKATKAN KEMAMPUAN BAHASA INGGRIS ANAK-ANAK PANTI ASUHAN KASIH IBU MELALUI RETELING STRATEGY - Fetriani; Eki Saputra (UNIVERSITAS SERAMBI MEKKAH, 2023)
The lack of full guidance is due to the limited ability of foster mothers who have to look after many other foster children. Although it cannot be denied that orphanage institutions have certainly tried their best to help the development of their foster children. This is the reason why dedication must be carried out. This service aims to motivate orphanage children to continue learning to gain knowledge and insight into English. The method of implementing activities carried out by the service team is the training method. In the implementation process, this activity begins by explaining the material, which is then divided into groups for them to discuss the material provided. This service activity went well according to plan. Service members found several challenges but they could be overcome. Students are actively involved and participative during the activity